P1 Epigenetic Regulation in Leaves of High Altitude Maize Landraces: Effect of UV-B Radiation - Rius, Sebastián P.; Emiliani, Julia; Casati, Paula (Frontiers in Plant Science, 2016)
P1 is a R2R3-MYB transcription factor that regulates the accumulation of a specific group of flavonoids in maize floral tissues, such as flavones and phlobaphenes. P1 is also highly expressed in leaves of maize landraces adapted to high altitudes and higher levels of UV-B radiation. In this work, we analyzed the epigenetic regulation of the P1 gene by UV-B in leaves of different maize landraces. Our results demonstrate that DNA methylation in the P1 proximal promoter, intron1 and intron2 is decreased by UV-B in all lines analyzed; however, the basal DNA methylation levels are lower in the landraces than in B73, a low altitude inbred line. DNA demethylation by UV-B is accompanied by a decrease in H3 methylation at Lys 9 and 27, and by an increase in H3 acetylation. smRNAs complementary to specific regions of the proximal promoter and of intron 2 3' end are also decreased by UV-B; interestingly, P1 smRNA levels are lower in the landraces than in B73 both under control conditions and after UV-B exposure, suggesting that smRNAs regulate P1 expression by UV-B in maize leaves. Finally, we investigated if different P1 targets in flower tissues are also regulated by this transcription factor in response to UV-B. Some targets analyzed show an induction in maize landraces in response to UV-B, with higher basal expression levels in the landraces than in B73; however, not all the transcripts analyzed were found to be regulated by UV-B in leaves.